Chikaku : Zeit und Erinnerung in Japan. - Ito, Toshiharu; Frisinghelli, Christine; Pakesch, Peter; Sei Watanabe, Makoto; Imafuku, Ryuta; Wilkoszewska, Krystyna; Tawada, Yoko; Kunsthaus Graz am Landesmuseum Joanneum in Graz; Museo de Arte Contemporanea de Vigo, Vigo (Cologne : Walther König, 2005)
Fujihata, Masaki ; Hidaka, Rieko ; Ito, Takashi ; Kasahara, Emiko ; Kawamata, Tadashi ; Kusama, Yayoi ; Minh-ha, Trinh T. ; Moriwaki, Hiroyuki ; Moriyama, Daido ; Nakamura, Tetsuya ; et al.
Kunsthaus Graz, Camera Austria, Graz, 04.06 - 11.09.2005 / Museo de Arte Contemporanea de Vigo, Vigo, 07.10.2005 - 22.01.2006
kunstcatalogus
Keywords: Japan